Missionary zeal and institutional control : organizational contradictions in the Basel Mission on the Gold Coast, 1828-1917 - Miller, Jon, 1940- (Grand Rapids, Michigan : William B. Eerdmans, 2003)
Rev. ed. of:The social control of religious zeal
Includes bibliographical references (p. 231-245) and index
Keywords: Evangelische Missionsgesellschaft in Basel -- History; Missions, Swiss -- Ghana -- History; Missions, German -- Ghana -- HIstory; Ghana -- Church history